Fenomena Perilaku Masyarakat Dalam Tradisi Malam Selawe di Makam Sunan Giri, Gresik - Moh. Dava Adhitya Mahesa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Malam Selawe tradition is one of the religious cultural practices that lives in Gresik society and still survives amid the swift flow of modernity. The research aims to understand the implementation, social interaction, motives for community behavior, and the influence of social media on the sustainability of the tradition. The research used descriptive qualitative. The results showed that the implementation of Malam Selawe as a religious ritual event as well as a social space that strengthens community cohesion and solidarity. The interactions that occur during the tradition reflect a culturally derived collective habitus. The motives for community participation are very diverse, ranging from religious values, habits, to affective and practical reasons. Social media plays an important role in the transformation and preservation of this tradition, especially among the younger generation. Their involvement in the tradition includes both physical presence and digital expression through various social media platforms. They use these media to share their experiences, convey spiritual messages and extend the reach of the tradition to a wider audience. Tradition has proven to be a flexible and adaptive platform that maintains spiritual values while being open to new forms of participation. It continues to live as a space for the actualization of religious and social values that are relevant to the times.